Resonant energy transfer and collectively driven emitters in waveguide QED - Cornelis Jacobus van Diepen; Vasiliki Angelopoulou; Oliver August Dall'Alba Sandberg; Alexey Tiranov; Ying Wang; Sven Scholz; Arne Ludwig; Anders Søndberg Sørensen; Peter Lodahl (Physical Review Research)
Waveguide quantum electrodynamics (QED) has opened a new frontier in quantum optics, which enables the radiative coupling of distantly located emitters via the spatially extended waveguide mode. This coupling leads to modified emission dynamics and previous work has reported the observation of increased intensity correlations (an antidip) when probing the resonance response of multiple emitters. However, the interference between independent emitters has been shown to lead to a similar response. Here, we directly observe resonant energy transfer between two distant quantum emitters by recording an antidip in the intensity correlations, g^{(2)}(τ), while driving only one of the emitters. Under the condition that only a single emitter is driven, the antidip in photon coincidences is a distinctive signature of emitter-emitter coupling, which enables the transfer of energy from the driven to the undriven emitter. Interestingly, the observed mechanism is a long-range and waveguide-engineered version of resonant Förster transfer, which is responsible for the transport of energy between chlorophylls in the photosynthesis. Building on the established coupling, we demonstrate collective driving of the coupled emitter pair. Specifically, we control the relative driving phase and amplitude of the emitters and apply this collective excitation scheme to selectively populate the long-lived subradiant state. This results in suppressed emission, i.e., the peculiar situation where driving two emitters as opposed to one effectively reduces the probability of photon emission. Our work presents novel emission regimes and excitation schemes for a multiemitter waveguide QED system. These can be exploited to deterministically generate emitter-emitter entanglement and advanced photonic states providing robustness against losses for photonic quantum computation and quantum communication.